Dynamic linkage between renewable and conventional energy use, environmental quality and economic growth: Evidence from Emerging Market and Developing Economies - Le Hoang Phong; Samuel Asumadu Sarkodie (Energy Reports, 2020)
The role of renewable and fossil fuel energy consumption on environmental sustainability remains inconclusive due to varied economic and technological structure. This study provides new insight by assessing the nexus between the utilization of two energy categories - renewable and conventional, environmental quality and economic growth embodying~capital, trade openness and government expenditure. A panel data of 45 Emerging Market and Developing Economies (EMDEs) from 1990 to 2014 was employed in the study. We applied heterogeneous panel data approach and second-generational econometric techniques that permit cross-sectional dependence and slope heterogeneity. The evaluation of long-term effects conducted by AMG, along with CCEMG and MG estimators revealed that besides other factors such as government expenditure, capital, and trade openness, non-renewable and renewable energy utilization significantly contributes to the economic growth of the selected EMDEs. The study acknowledges the trade-off effect between environmental quality and economic growth. Using Dumitrescu and Hurlin test, we found strong evidence to support the feedback hypotheses among renewable energy, consumption of conventional fuels, economic growth and CO2 emissions. From a policy perspective, the empirical findings recommend the implementation of effective policies that promote green power and economic structural adjustment in order to diminish the level of atmospheric CO2 emissions.
Keywords: C23; Q40; Q55; Q56; 330; Sustainable development; Economic growth; Conventional energy use; Environmental quality; Renewable energy usage